Should the ART trial change our practice? - Villar, Jesús; Suárez-Sipmann, Fernando; Kacmarek, Robert M. (Journal of Thoracic Disease, 2017)
Acute respiratory distress syndrome (ARDS) is one of the most severe forms of acute hypoxemic respiratory failure. Caused by pulmonary or systemic insults, is characterized clinically by hypoxemia that does not respond to the administration of high concentrations of oxygen (FiO2) and by the presence of bilateral infiltrates on chest imaging due to high-permeability pulmonary edema (1). An integral part of the supportive therapy of ARDS is the application of mechanical ventilation (MV). The goal of MV is to achieve adequate gas exchange and tissue oxygenation without further damaging the lungs. Since the first description of ARDS in 1967 (2), the use of positive end-expiratory pressure (PEEP) has been adopted as standard practice for its ventilatory management. PEEP prevents end-expiratory alveolar collapse. The pivotal ARDSnet trial published in 2000 (3) demonstrated that a “lung-protective” MV strategy using a tidal volume (VT) of 4–8 mL/kg of predicted body weight (PBW) and moderate levels of PEEP improved survival. Since then, limitation of VT to less than 8 ml/kg PBW and plateau pressure to less than 30 cmH2O, and application of PEEP between 10 to 20 cmH2O represents the standard for MV in ARDS.